Purchasing Power Under Pressure: Examining the 12% VAT Increase Amid Indonesia's Economic Recovery - Rasiman; Prasetia, Angga; Rizqi, Muhamad Nur; Mauludin, Ilyas (INOVATOR, 2025)
This study analyzes the impact of the increase in Value Added Tax (VAT) rates from 11% to 12% on the purchasing power of the Indonesian people. Using a quantitative-descriptive approach, this study observes how these policies affect consumption patterns, inflation, and general public welfare. The results of the study show that the low-income group is the most affected by this policy. The government has made efforts to reduce the negative impact by providing subsidies and other fiscal incentives. However, this analysis shows that these measures are still not fully effective